Characterizing Quantumness via Entanglement Creation - Gharibian, Sevag; PIANI, MARCO; ADESSO, GERARDO; CALSAMIGLIA, JOHN; HORODECKI, PAWEŁ (International Journal of Quantum Information)
In [Piani et al., PRL106 (2011) 220403], an activation protocol was introduced which maps the general non-classical (multipartite) correlations between given systems into bipartite entanglement between the systems and local ancillae by means of a potentially highly entangling interaction. Here, we study how this activation protocol can be used to entangle the starting systems themselves via entanglement swapping through a measurement on the ancillae. Furthermore, we bound the relative entropy of quantumness (a naturally arising measure of non-classicality in the scheme of Piani et al. above) for a special class of separable states, the so-called classical–quantum states. In particular, we fully characterize the classical–quantum two-qubit states that are maximally non-classical.

Approximation Algorithms for QMA-Complete Problems - Gharibian, Sevag; Kempe, Julia (IEEE Annual Conference on Computational Complexity (CCC 2011))
Approximation algorithms for classical constraint satisfaction problems are one of the main research areas in theoretical computer science. Here we define a natural approximation version of the QMA-complete local Hamiltonian problem and initiate its study. We present two main results. The first shows that a non-trivial approximation ratio can be obtained in the class NP using product states. The second result (which builds on the first one), gives a polynomial time (classical) algorithm providing a similar approximation ratio for dense instances of the problem. The latter result is based on an adaptation of the "exhaustive sampling method" by Arora et al. [J. Comp. Sys. Sci. 58, p.193 (1999)] to the quantum setting, and might be of independent interest.

All Nonclassical Correlations Can Be Activated into Distillable Entanglement - Piani, Marco; Gharibian, Sevag; Adesso, Gerardo; Calsamiglia, John; Horodecki, Paweł; Winter, Andreas (Physical Review Letters)
We devise a protocol in which general nonclassical multipartite correlations produce a physically relevant effect, leading to the creation of bipartite entanglement. In particular, we show that the relative entropy of quantumness, which measures all nonclassical correlations among subsystems of a quantum system, is equivalent to and can be operationally interpreted as the minimum distillable entanglement generated between the system and local ancillae in our protocol. We emphasize the key role of state mixedness in maximizing nonclassicality: Mixed entangled states can be arbitrarily more nonclassical than separable and pure entangled states.

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Weighted Distribution of the 4-rank of Class Groups and Applications - Fouvry, Étienne; Klüners, Jürgen (International Mathematics Research Notices)
We prove that the distribution of the values of the 4-rank of ideal class groups of quadratic fields is not affected when it is weighted by a divisor type function. We then give several applications concerning a new lower bound of the sums of class numbers of real quadratic fields with discriminant less than a bound tending to infinity and several questions of P. Sarnak concerning reciprocal geodesics.
Keywords: General Mathematics

Generating subfields - van Hoeij, Mark; Klüners, Jürgen; Novocin, Andrew (Journal of Symbolic Computation)
Given a field extension K/k of degree n we are interested in finding the subfields of K containing k. There can be more than polynomially many subfields. We introduce the notion of generating subfields, a set of up to n subfields whose intersections give the rest. We provide an efficient algorithm which uses linear algebra in k or lattice reduction along with factorization in any extension of K. Implementations show that previously difficult cases can now be handled.
Keywords: Computational Mathematics; Algebra and Number Theory

Foundations of Critical Media and Information Studies - Fuchs, Christian

The Political Economy of WikiLeaks: Power 2.0? Surveillance 2.0? Criticism 2.0? Alternative Media 2.0? - Fuchs, Christian (Global Media Journal – Australian Edition: Contribution to the Special Issue on “WikiLeaks: Journalism and the 21st Century Mediascape“ (edited by Hart Cohen and Antonio Castillo))

An Alternative View of Privacy on Facebook - Fuchs, Christian (Information: [special issue on “Trust and privacy in our networked world“, edited by Dieter M. Arnold and Herman T. Tavani])

Web 2.0, Prosumption, and Surveillance. [special issue on “Marketing, consumption and surveillance”, edited by Jason Pridmore and Detlev Zwick] - Fuchs, Christian (Surveillance & Society)

Towards an Alternative Concept of Privacy - Fuchs, Christian (Journal of Information, Communication and Ethics in Society)

A Contribution to the Critique of the Political Economy of Google - Fuchs, Christian (Fast Capitalism)

The Contemporary World Wide Web: Social Medium or New Space of Accumulation? - Fuchs, Christian (The Political Economies of Media. The Transformation of the Global Media Industries)

Cognitive Capitalism or Informational Capitalism? The Role of Class in the Information Economy - Fuchs, Christian (Cognitive Capitalism, Education and Digital Labor)

Two New Critical Internet Studies-Books: Marcus Breen’s “Uprising” and Eran Fisher’s “Media and New Capitalism in the Digital Age” - Fuchs, Christian (tripleC – Journal for a Global Sustainable Information Society)

Critical Media and Communication Studies Today. A Conversation - Fuchs, Christian; Winseck, Dwayne (tripleC)

"BlackBerry-Riots": Gewalt hat andere Gründe [“BlackBerry-Tiots“: Violence has Other Causes“] - Fuchs, Christian (Futurezone)

“Twitter Mobs“ and the Structural Violence of Neoliberalism - Fuchs, Christian (Counterfire)

Review of “The problem of order in the global age. Systems and mechanisms“ (Andreas Pickel) - Fuchs, Christian (Philosophy of the Social Sciences)

‚Grundlegende Betrachtungen zur Technik – Technomorphologische Analysen des Textilen’ - Kraft, Kerstin

‚Glamour und Grauen. Das Erforschen und Ausstellen von Bekleidung aus den 1930er und 1940er Jahren’ - Kraft, Kerstin

Cutting Patterns - Kraft, Kerstin

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

Towards a Critical Theory of Surveillance Studies - Allmer, Thomas

Critical Surveillance Studies in the Information Society - Allmer, Thomas (tripleC)

Bildung MACHT Gesellschaft

Study on the Performance Enhancement of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fábio Fedrizzi; Wirth, Gilson Inácio; Wolff, Karsten; Hilleringmann, Ulrich (ECS Transactions)
Due to the electrical, sensory and optical properties the interest on ZnO-based devices including thin-film transistors (TFT) aroused. The main concerns, when using ZnO nanoparticles (NP-ZnO) in TFT, are the low charge carrier mobility and the hysteresis when poly(4-vinylphenol) (PVP) is used as gate dielectric. It is well-known that the mobility in NP-ZnO films can be enhanced by the subsequent hydrothermal decomposition of zinc salts. The electrical behavior as a function of time and temperature is investigated, taking the NP-ZnO without addition of zinc acetate as reference. The addition of zinc acetate leads to a device with better performance, with increased drain current level and without the presence of the hysteresis in the transfer characteristic. The formation reaction was performed at a temperature of 200°C, which enables process compatibility to some plastic substrates.
Keywords: General Medicine

Solution processed inverter based on zinc oxide nanoparticle thin-film transistors with poly(4-vinylphenol) gate dielectric - Wolff, K.; Hilleringmann, Ulrich (Solid-State Electronics)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Characterization of SiON integrated waveguides via FTIR and AFM measurements - Frers, Torsten; Hett, Thomas; Hilleringmann, Ulrich; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (2011 Semiconductor Conference Dresden)

Modeling and simulation of arbitrary ordered nonlinear charge-pump phase-locked loops - Wiegand, C.; Hangmann, C.; Hedayat, C.; Hilleringmann, Ulrich (2011 Semiconductor Conference Dresden)

Semiconductor nanoparticles for electronic device integration on foils - Hilleringmann, Ulrich; Wolff, K.; Assion, F.; Vidor, F. F.; Wirth, G. I. (IEEE Africon '11)

Plane wave spectrum expansion from near-field measurements on no-planar lattices - Reinhold, C; Hangmann, C; Mager, T; Hedayat, C; Hilleringmann, Ulrich (Proc. 5th Int. Conf. on electromagnetic Near-field Characterization and Imaging (ICONIC) 2011)

Krisen der Autorschaft bei Bruckner und Reger als Insignien der beginnenden musikalischen Moderne - Höink, Dominik; Jacob, Andreas (Autorschaft. Ikonen – Stile – Institutionen)

Anton Bruckner und Franz Liszt. Zur Konstruktion kirchenmusikalischer Idealbilder - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

Calculus-based optimization of the electron dynamics in nanostructures - Meier, Torsten; Reichelt, Matthias; Walther, A. (Photonics and Nanostructures - Fundamentals and Applications)
For numerous applications, the computation and provision of exact derivative information plays an important role for optimizing the considered system. This paper introduces the technique of algorithmic differentiation, a method to compute derivatives of arbitrary order within working precision. This derivative information will be combined with a calculus-based optimization algorithm to optimize a non-trivially shaped laser pulse which coherently steers the electron dynamics in a semiconductor quantum wire. Numerical results illustrating the cost for the derivative computation and the optimization process are presented and discussed.

Nachhaltiger Konsum. Neoliberale Subjekte zwischen grünem Lifestyle und gesellschaftlicher Verantwortung - Hälterlein, Jens (Gesellschaftliche Ökologie. Beiträge zur Konstruktion geographischer Wirklichkeiten. Sozialgeographische Manuskripte)

Weder Konsumismus noch Askese – Interpassivität! Über das kritische Potential des SUV-Fahrens - Hälterlein, Jens (Wir sind nie aktiv gewesen. Interpassivität zwischen Kunst- und Gesellschaftskritik)

Zwischen Sprachspiel und Methode. Perspektiven der Diskursanalyse - Feustel, Robert; Schochow , Maximilian (BEHEMOTH A Journal on Civilisation)

Finite Symplectic Matrix Groups - Kirschmer, Markus (Experimental Mathematics)
This paper classifies the maximal finite subgroups of SP₂ₙ(Q) for 1⩽n⩽11 up to GL₂ₙ(Q) conjugacy in .
Keywords: General Mathematics

Kommentar aus religionspädagogischer Sicht - Hymnologiedidaktische Überlegungen - Schroeter-Wittke, Harald (Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden)

Auf der Suche nach der Identität Europas - Kultur als transformatorische Kraft - Schroeter-Wittke, Harald (Perspektiven für ein Europa im Zeitalter der Globalisierung. 60 Jahre Evangelische Akademie Villigst / Iserlohn)

Den Schein wahren. Neun Responsorien auf das praktisch-theologische Interesse an den Oberflächen - Schroeter-Wittke, Harald (Lebenswissenschaft Praktische Theologie?)

Schaut hin! Rede für die Gedenkfeier am 2. April 2008 - Schroeter-Wittke, Harald (So fern und doch so nah... Wider das Vergessen)

Wewelsburg - Religionssensibilität an einem Ort des Schreckens - Schroeter-Wittke, Harald; Arnhold, Oliver (Religionssensible Schulkultur)

Hochkultur oder Popkultur? - Schroeter-Wittke, Harald; Marti, Andreas (Reformierte Liturgik - kontrovers)

Religionssensible Musik - Eine Klangreise - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Was ist Religionssensibilität? - Schroeter-Wittke, Harald (Religionssensible Schulkultur)

Intensity dependence of optically-induced injection currents in semiconductor quantum wells - Pochwala, Michal; Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (CLEO:2011 - Laser Applications to Photonic Applications)
The intensity dependence of optically-induced injection currents in semiconductor quantum wells is investigated numerically. Oscillatory behavior of the electron charge current transients as function of intensity and time is predicted and explained.
Keywords: tet_topic_qw

Simulation of Mutual Coupling of Photonic Crystal Cavity Modes and Semiconductor Quantum Dots - Declair, S.; Song, X.; Meier, Torsten; Förstner, Jens (THE FOURTH INTERNATIONAL WORKSHOP 2011)
We present numerical results of the mutual coupling between photonic crystal cavities and semiconductor quantum dots. Normal mode splitting between a single cavity mode and a single quantum dot is shown under weak excitation, while under strong excitation Q‐factor dependent side bands appear, according to the AC‐Stark effect. Coupled photonic crystals, aligned parallel but displaced under a 30°‐angle for efficient coupling, show line splittings of all eigenmodes, if a single eigenmode is resonantly coupled to a single quantum dot. The mutual coupling of N resonant quantum dots to a single cavity mode results in a N−−√ scaling of the splitting, known from quantum optics, but corrected by the field amplitude fraction for not collocated quantum dots.
Keywords: tet_topic_phc; tet_topic_qd